Factores Biosocioculturales y Prácticas Maternas en niños Menores de 1 año con Iras no Neumónicas, C.S.Alto Trujillo-2012 - La Rosa Villar, Milagros Janeth (2013)
The present study is a descriptive correlational research was conducted during the months of October to December of 2012 with mothers of children under 1 year with IRAs pneumonic not treated at the CS High Trujillo, in order to determine the relationship between the factors and the maternal practices biosocioculturales on non-pneumonic IRAs. The sample consisted of 100 mothers selected according to inclusion criteria. Data collection was obtained by applying the "Questionnaire biosocioculturales factors and maternal practices on non-pneumonic wrath (CFBPMIN)". The data were tabulated, processed in SPSS version 15 and presented in single and double entry table. The information obtained was processed and analyzed by the test of independence of criteria Chi square (X2). We conclude that most of the mothers were between 20-39 years (72%), 37 percent housewives, 43 percent secondary education level and 46 per cent level of knowledge about IRAs medio. Las maternal practices pneumonic not in children under 1 year were adequate in 68 percent. Maternal practices on non-pneumonic IRAs in children under 1 year showed significant relationship with the level of education and level of knowledge. Key Words: No pneumonic IRAs, biosociocultural factors and maternal practices.